1981
DOI: 10.1021/bi00525a019
|View full text |Cite
|
Sign up to set email alerts
|

Lactose carrier protein of Escherichia coli: interaction with galactosides and protons

Abstract: The binding of galactosides to the lactose carrier of cytoplasmic membrane vesicles derived from Escherichia coli strains T185 or T206 which harbor plasmids bearing the lacy gene is measured and compared to the active transport of galactosides in vesicles or cells of the haploid strain ML308-225 in terms of the apparent affinity. Lactose and other galactosides bind only to a single site on the carrier protein, The affinity of lactose for this site is low (KO = 14 f 5 mM), while the half-saturation constant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 44 publications
10
54
0
Order By: Relevance
“…We found that precipitated LPase does not show the slow MalNPyr fluctuations. (ii) Below the lipid-phase transition the transport rate is decreased drastically (7)(8)(9), although binding is unaltered in consonance with unaltered secondary structure (6). Here, we found a reduced relaxation rate of the slow MalNPyr fluctuations together with a reduced amplitude.…”
Section: Analysis and Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We found that precipitated LPase does not show the slow MalNPyr fluctuations. (ii) Below the lipid-phase transition the transport rate is decreased drastically (7)(8)(9), although binding is unaltered in consonance with unaltered secondary structure (6). Here, we found a reduced relaxation rate of the slow MalNPyr fluctuations together with a reduced amplitude.…”
Section: Analysis and Discussionsupporting
confidence: 53%
“…3). This condition is fulfilled in our case because the temperature dependence of the transport rate obeys an Arrhenius relation (9,28). A transport cycle involves two conformational changes, one with bound substrate and one without.…”
Section: Analysis and Discussionmentioning
confidence: 82%
“…The activity of membrane proteins often exhibits a break at Tt with a low activation energy above Tt and a high activation energy below Tt (30,31). One is tempted to interprete this behavior by postulating that protein activity requires a fluid lipid environment.…”
Section: Total Free Energy and Enthalpy Changementioning
confidence: 99%
“…In addition, the membranes become leaky, components leak that are prerequisite for life. With quasi-crystalline membranes life is not possible [1] [2]. Cells regulate the transition temperature of their membranes with variation of components.…”
Section: Discussionmentioning
confidence: 99%